Pelayanan Kesehatan Telinga Hidung Tenggorok Pada Masyarakat Pesisir di Wilayah Kerja Puskesmas Tanjung Karang - Yuliyani, Eka Arie; Kadriyan, Hamsu; Yudhanto, Didit; Susilawati, Ni Ketut; Prasetayningrum, Ika; Rarasati, Rista Rahayu; Pratama, Lalu Aditya Haris (Universitas Mataram, 2023)
Until now, ENT disease is still a health problem that needs special attention, especially in coastal areas. This can have an impact on various sectors of life both socially, economically, schools and also the quality of life, so it is very necessary to make efforts to improve health status through easy and affordable access to health services. Coinciding with the commemoration of World Cancer Day, ENT Specialists gathered in PERHATI-KL Cab. NTB carried out health social service activities in the western coastal area of ​​Lombok Island. The purpose of this activity is to provide ear health services to the Coastal Communities in Tanjung Karang which include health services in the ENT sector, namely ear cleaning, ENT and head and neck examinations, medication and audiometric examinations. This Social Service activity was attended by approximately 36 people from the community around the Tanjung Karang coastal area. The most dominant health problem was cerumen obturans (36.1%) which occurred in both children and adults, followed by CSOM, Rhinitis, Tinnitus, Pharyngitis, Otitis Externa and others within normal limits. The community is very enthusiastic and welcomes this Social Service activity, because they get direct health services from ENT-KL Specialists and can also consult about various kinds of complaints in the ENT field. The data obtained in this activity can be used as a general description of the health status of coastal communities in the west of Lombok Island.